The world we are fighting for - Tobocman, Seth 1958-; Kuper, Peter 1958- (AK Press, 2020)
A visual journey through our broken world and, most importantly, how we're fixing it
Keywords: Radicalism -- United States -- Comic books, strips, etc; Radikalismus; Politik; Soziale Gerechtigkeit; USA; Comic